2021
DOI: 10.1016/j.meegid.2021.104973
|View full text |Cite
|
Sign up to set email alerts
|

Global variation in SARS-CoV-2 proteome and its implication in pre-lockdown emergence and dissemination of 5 dominant SARS-CoV-2 clades

Abstract: SARS-CoV-2 is currently causing major havoc worldwide with its efficient transmission and propagation. To track the emergence as well as the persistence of mutations during the early stage of the pandemic, a comparative analysis of SARS-CoV-2 whole proteome sequences has been performed by considering manually curated 31,389 whole genome sequences from 84 countries. Among the 7 highly recurring (percentage frequency≥10%) mutations (Nsp2:T85I, Nsp6:L37F, Nsp12:P323L, Spike:D614G, ORF3a:Q57H, N protein:R203K and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…In our results, some COVID-19 mutations associated with mild disease were also found, such as nsp14:I164ILV, ORF8:L84S, nsp4:F308Y, nsp6:L37F, ORF3a:G196V, N:P13L, nsp4:M324I, and N:G204R. These mutations tend to be present in low-risk patients with different combinations, and some have been reported to be associated with mild disease or disease transmissibility [ 55 , 60 ].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In our results, some COVID-19 mutations associated with mild disease were also found, such as nsp14:I164ILV, ORF8:L84S, nsp4:F308Y, nsp6:L37F, ORF3a:G196V, N:P13L, nsp4:M324I, and N:G204R. These mutations tend to be present in low-risk patients with different combinations, and some have been reported to be associated with mild disease or disease transmissibility [ 55 , 60 ].…”
Section: Discussionsupporting
confidence: 52%
“…D614G is a hotspot mutation that appeared as early as the Alpha variant, and although the D614G mutation does not directly correlate with disease severity, other COVID-19 variants containing this mutation may accelerate infection due to the ability to facilitate viral entry into cells and further aggravate the disease [ 54 , 59 ]. ORF3a:Q57H and nsp2:T85I first appeared in the Beta variants and our results suggest that they may be associated with severe outcomes of SARS-CoV-2 infection [ 60 ]. Studies have shown that SNP:C241T mutation is associated with lower viral replication efficiency [ 61 ] and it can be observed in our results that mild patients with SNP:C241T mutation tend to be combined with less other severe mutation features (e.g., nsp2:T85I, ORF3a:Q57H, and V1176F), which suggests that this gene mutation may be indirectly associated with mild COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…146 Notably, the increased transmissibility and pathogenicity of some SARS-CoV-2 variants are closely related to Nsp2 mutations, such as T85I of Nsp2 in the B.1.526/B.1.427/B.1.429 variant. 147 149 The presumed explanation is that mutations interfere with the interaction between Nsp2 and host proteins, 141 ultimately affecting virulence. The immunogenicity of Nsp2 can be applied to the development of inactive or live attenuated virus vaccine.…”
Section: Nonstructural Proteins Of Sras-cov-2mentioning
confidence: 99%
“…For this, the gene sequences corresponding to the uORFs were translated using the reference sequences (36) with the help of in-house scripts. The amino acid mutation analyses were done as discussed elsewhere (9,10). The mutations were categorized as highly recurring (HR, occurring with ≥10% percentage frequency), moderately recurring (MR, occurring with 1%-10% percentage frequency), and low recurring (LR, occurring below 1% percentage frequency but should have occurred at least three times) based on their recurrence in the 775,392 viral proteomes.…”
Section: Determination Of Sars-cov-2 Uorf Sequence Conservationmentioning
confidence: 99%
“…Indeed, there are reports (7,8) about the reduced efficacy of the vaccines against the new variants (4). Reports indicate that the number of mutations in the spike protein has increased to 1.4-fold in a time span of 6 months (9,10). This is indicative of challenges in using the existing spike protein antigen-based vaccines (11) when new variants emerge.…”
Section: Introductionmentioning
confidence: 99%